Implementation of Accrual Basis Accounting in the Public Sector in Indonesia: A Literature Review - Amal, Muhammad Ichlasul; Nurfaliza, Nurfaliza; Wokas, Heince R. N. (East Asian Journal of Multidisciplinary Research, 2024)
This Literature Review aims the application of Accrual Accounting in the public sector in Indonesia. This research method uses SLR (Systematic Literature Review). Data analysis by mapping 30 selected journals from 2019 to 2023 in the Google Scholar database. The results of this research show the obstacle and key factors that influence the succession implementation of local government financial reports in Indonesia; Obstacles in implementing Accrual Basis Accounting include a lack of awareness on the part of management regarding the urgency of implementing it. , the information system is able to accommodate reporting and HR readiness both in terms of competency and capability. The Important factors that influence implementing Accrual Basis Accounting; human resource competence, information technology, internal control and regulations. The most common factors found were HR competency and Internal Control which had the greatest influence on the success of implementing Accrual Basis Accounting in the public sector in Indonesia.